Blowfish encryption on cloud data storage - Divya Priya, Degala; Shirisha, Bethala; Pravallika, B. (International Journal of Engineering and Technology, 2018)
Cloud computing stores large amount of data and it acts as a resource pool with a network of large number of computers. To secure large volumes of data stored in cloud we can make use encryption techniques. Encryption is used to encrypt the data into cipher data andsecurely transmit data in open networks. Each type of data has its own features, therefore different techniques should be used to protect confidential data from unauthorized access.We introduce a block-based transformation algorithm based on the combination of data and a well known encryption and decryption algorithm called Blowfish. In this paper we have discussed about cloud computing security issues, mechanism, challenges that cloud service provider face during cloud engineering and presented the metaphoric study of blowfish security algorithm.Â Â Â